2002
DOI: 10.1080/01650250143000481
|View full text |Cite
|
Sign up to set email alerts
|

Dear Santa: The effects of television advertising on young children

Abstract: The effects of television advertising Dear Santa: The effects of television advertising on young children. AbstractEvery day children are exposed to the selling messages of advertisers via the television.There is some debate in the literature over the age at which young children can distinguish television advertisements from programmes, when they can remember and want what they see and when they are able to understand that the advertiser's motive is to sell a product. Resolution of the debate has been hampered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 20 publications
1
43
0
3
Order By: Relevance
“…Advert exposure has been related to increased requests for certain products, 18 and this applies equally to food adverts as well as toy adverts. 19 A recent cross-cultural study involving many countries demonstrated a significant association between the advert exposure and childhood obesity. 20 Consumer segmentation intensifies child-oriented marketing.…”
Section: Discussionmentioning
confidence: 99%
“…Advert exposure has been related to increased requests for certain products, 18 and this applies equally to food adverts as well as toy adverts. 19 A recent cross-cultural study involving many countries demonstrated a significant association between the advert exposure and childhood obesity. 20 Consumer segmentation intensifies child-oriented marketing.…”
Section: Discussionmentioning
confidence: 99%
“…La présence du père Noël dans les centres commerciaux, les magasins de détail et les maisons à la grandeur presque des pays développés, d'octobre à décembre, fournit par ailleurs un fort renforcement visuel à la marque et son association avec la fête de Noël encourage manifestement la consommation, l'échange de cadeaux, les dépenses et la connectivité émotionnelle avec la marque, comme partie intégrante de ce qui est appelé l'« esprit de Noël » (Clarke, 2006 ; Pourtant, bien qu'il y ait une documentation abondante sur le père Noël en tant que marque (Otnes et al, 1994 ;O'Cass et Clarke, 2002 ;Pine et Nash, 2002 ;Snellman, 2006a ;Pine et al, 2007 ;Coca-Stefaniak et al, 2008), il y a peu de débats scientifiques concernant la contribution du père Noël sur le plan de la compétitivité des destinations de latitude Nord et sur les façons dont les différentes destinations ont cherché à s'approprier ce personnage . S'appuyant sur le développe-ment du village du père Noël à Rovaniemi dans le nord de la Finlande, Michael Pretes (1995) a notamment analysé le déve-loppement de l'« industrie du père Noël » en tant que forme de tourisme postmoderne.…”
Section: La Plus Grande Marque Au Mondeunclassified
“…Warren (2005) menar dock att även om snabbmat och TV-tittande kan påverka fetma och kost, krävs det en drastisk minskning av snabbmatsintaget för att kvaliteten på maten ska ha betydelse för att öka fetman (Warren, 2005). En studie av TV-reklamens effekter på unga barn i England visade att när barnen tittade på TV ensamma var de mer mottagliga för reklam än en grupp barn, som inte var utsatta för reklam (Pine & Nash, 2002). Det visade sig att jämförelsegruppen med barn från Sverige, där reklam riktad till barn inte är tillåtet, bad om betydligt färre antal leksaker och färre märkesvaror.…”
Section: Reklamunclassified